2024
DOI: 10.1039/d3ew00377a
|View full text |Cite
|
Sign up to set email alerts
|

Persulfate enhanced ciprofloxacin removal from water by laser-induced graphene-based electroconductive ultrafiltration membrane

Najmul Haque Barbhuiya,
Utkarsh Misra,
Bhavana Kanwar
et al.

Abstract: The ineffective removal of emerging pollutants by conventional treatment plants has necessitated the use of advanced treatment techniques such as electroconductive membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(36 citation statements)
references
References 82 publications
(162 reference statements)
1
19
0
Order By: Relevance
“…Previous studies have shown that sulfidation of nZVI decreases its reactivity with water and increases its reactive lifetime. , Thus, the sulfidation of nZVI and the S-nZVI incorporation into the LIG filters can improve the electrochemical activity and enhance the contaminant removal with good reusability compared to Fe-LIG filters. It is important to mention that these catalytic ECMs can be recycled or regenerated using various methods explored in literature including electrodeposition, electroreduction, and regeneration of catalytic surfaces. ,, …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that sulfidation of nZVI decreases its reactivity with water and increases its reactive lifetime. , Thus, the sulfidation of nZVI and the S-nZVI incorporation into the LIG filters can improve the electrochemical activity and enhance the contaminant removal with good reusability compared to Fe-LIG filters. It is important to mention that these catalytic ECMs can be recycled or regenerated using various methods explored in literature including electrodeposition, electroreduction, and regeneration of catalytic surfaces. ,, …”
Section: Resultsmentioning
confidence: 99%
“…For the in situ fouling monitoring, the ECM and the flexible stainless-steel sheet were sandwiched in a custom-made ECM cell. 28 The flexible stainless-steel sheet attached to the ECM cell acted as a counter/reference electrode, and the ECM acted as a working electrode. The circuit fitting of the Nyquist plot was performed using NOVA 2.1 software.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The ECM was fabricated via the PVA 2% solution coating method as per our previous study. 28 Briefly, the membrane substrate was prepared with a nonsolvent-induced phase inversion process followed by laser irradiation to get the LIG filter. The filter was then converted to an LIG-based ECM via the PVA coating method for fouling monitoring application (Figure 1a).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations